GaN-based schottky diode with vertical algan / gan heterojunction and method of fabricating the same
Patent Information
- Application Number
- CN202310293807.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-24
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-03-24
AI Technical Summary
Existing technologies produce vertical junction barrier Schottky diodes with low breakdown voltage, high reverse leakage current, and low forward current.
A vertical AlGaN/GaN heterojunction is formed by etching grooves on N+-GaN and N--GaN layers and growing AlGaN layers on them. Two-dimensional electron gas (2DEG) is formed in the vertical direction using the AlGaN layer to reduce the equivalent resistance of the N--GaN layer, while no 2DEG is formed in the horizontal direction. An anode is fabricated by etching an anode groove on the top surface of the N--GaN layer.
This improves the forward current density and frequency characteristics of the diode, and enhances the current density per unit area and area utilization.
Smart Images

Figure CN116631866B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of microelectronic device technology and relates to a GaN-based Schottky diode and its fabrication method, specifically to a GaN-based Schottky diode with a vertical AlGaN / GaN heterojunction and its fabrication method. Background Technology
[0002] With the gradual maturation of semiconductor technology, third-generation semiconductor materials, represented by GaN, SiC, and semiconductor diamond, have emerged and gradually become a research hotspot in the semiconductor industry. Compared with traditional semiconductor materials, gallium nitride (GaN) materials have a large bandgap (3.4 eV), high breakdown field strength (3.3 MV / cm), good chemical stability, high operating temperature, high breakdown voltage, and low on-resistance. These characteristics compensate for the shortcomings of the first two generations of semiconductor materials. Therefore, GaN has good application prospects in high-temperature and high-voltage applications. Currently, GaN diodes have been applied in aerospace, autonomous driving, and wireless power transmission.
[0003] GaN diodes are mainly classified into lateral and vertical structures. In conventional lateral structures, current collapse and self-heating effects are significant issues limiting device development. Compared to lateral structure devices, vertical GaN diodes, for the same device size, exhibit higher current density, with current primarily transported within the GaN material. When the device is reverse biased, the internal electric field distribution is more uniform, resulting in higher reverse breakdown voltage and greater reliability.
[0004] Schottky diodes, as a basic two-terminal device, have advantages such as low turn-on voltage and high switching frequency, and are widely used in rectification, detection, and limiting. Their development is trending towards higher breakdown voltage, higher on-state ratio, and lower on-resistance. However, existing vertical junction barrier Schottky diodes exhibit low breakdown voltage, high reverse leakage current, and low forward current.
[0005] In view of the above-mentioned technical defects of the prior art, there is a need to provide an improved GaN-based vertical Schottky diode and its fabrication method to overcome the above defects. Summary of the Invention
[0006] To overcome the shortcomings of existing technologies, this invention proposes a GaN-based Schottky diode with a vertical AlGaN / GaN heterojunction and its fabrication method, which can reduce the equivalent resistance of the drift layer, increase the current density per unit area and the area utilization rate, thereby improving the forward current density of the diode.
[0007] To achieve the above objectives, the present invention provides the following technical solution:
[0008] A method for fabricating a GaN-based Schottky diode with a vertical AlGaN / GaN heterojunction, characterized by comprising the following steps:
[0009] 1) In N with a thickness of 1~4μm + - An N layer with a thickness of 3~9μm is grown on the front side of the GaN layer. - -GaN layer;
[0010] 2) In the N + -GaN layer and N - - Trenches are etched on the GaN layer, the width of which is 3~5μm and the depth is such that the N is deposited thereon. + - The GaN layer was etched away by 100~500 nm;
[0011] 3) Grow an AlGaN layer with a thickness of 10~40nm throughout;
[0012] 4) In the N + - The cathode is fabricated on the bottom surface of the GaN layer;
[0013] 5) Deposit a dielectric layer with a thickness of 0.1~1μm on the AlGaN layer;
[0014] 6) Etch away the N located in the N - The portion above the GaN layer consists of the AlGaN layer and the dielectric layer, exposing the N-type GaN layer. - -Top surface of the GaN layer;
[0015] 7) In the exposed N - - An anode groove is etched on the top surface of the GaN layer, and the depth of the anode groove is 300-900nm;
[0016] 8) An anode is formed in the anode groove and on the remaining dielectric layer.
[0017] Preferably, the Al composition of the AlGaN layer is 15% to 50%.
[0018] Preferably, the dielectric layer is an Al2O3 layer, a SiN layer, or a SiO2 layer.
[0019] Preferably, the AlGaN layer and the N - - A two-dimensional electron gas is formed between GaN layers in the vertical direction, but not in the horizontal direction.
[0020] Preferably, the cathode is composed of a Ti layer, an Al layer, a Ni layer and an Au layer stacked together, wherein the thickness of the Ti layer is 20 nm, the thickness of the Al layer is 160 nm, the thickness of the Ni layer is 55 nm and the thickness of the Au layer is 45 nm.
[0021] Preferably, after step 4), a rapid metal annealing process is performed first, followed by step 5), wherein the rapid metal annealing process is a rapid thermal annealing at 870°C in a N2 atmosphere for 30 seconds.
[0022] Preferably, the anode is composed of a Ni layer and an Au layer stacked together, wherein the Ni layer has a thickness of 45 nm and the Au layer has a thickness of 200 nm.
[0023] Furthermore, the present invention also provides a GaN-based Schottky diode with a vertical AlGaN / GaN heterojunction, characterized in that it is prepared using the above-described preparation method.
[0024] Compared with the prior art, the GaN-based Schottky diode with a vertical AlGaN / GaN heterojunction and its fabrication method of the present invention have one or more of the following beneficial technical effects:
[0025] 1. Compared to traditional GaN-based vertical diodes, this invention utilizes a regrown AlGaN layer to form a 2DEG (two-dimensional electron gas) in the vertical direction, reducing N0. - The equivalent resistance of the GaN layer increases the forward current density of the diode; at the same time, the high electron mobility of 2DEG gives the diode better frequency characteristics.
[0026] 2. Compared with the horizontal conductivity of traditional AlGaN / GaN diodes, this invention adopts vertical 2DEG channel conductivity, which increases the current density per unit area and thus improves the area utilization of the diode. Attached Figure Description
[0027] Figure 1 It is N + -Schematic diagram of the GaN layer structure.
[0028] Figure 2 Is Figure 1 N was grown on the basis + -Schematic diagram of the structure behind the GaN layer.
[0029] Figure 3 Is Figure 2 The diagram shows the structure after the grooves were etched.
[0030] Figure 4 Is Figure 3 This is a schematic diagram of the structure after an AlGaN layer has been grown on top of the existing structure.
[0031] Figure 5 Is Figure 4 Based on this, a schematic diagram of the structure after the cathode was created.
[0032] Figure 6 Is Figure 5 This is a schematic diagram of the structure after a medium layer has been grown on top of the existing structure.
[0033] Figure 7 Is Figure 6 This is a schematic diagram of the structure after etching away part of the dielectric layer and the AlGaN layer.
[0034] Figure 8 Is Figure 7 The diagram shows the structure after etching the anode groove.
[0035] Figure 9 Is Figure 8 Based on this, a schematic diagram of the structure after anode was created. Detailed Implementation
[0036] The present invention will be further described below with reference to the accompanying drawings and embodiments. The content of the embodiments is not intended to limit the scope of protection of the present invention.
[0037] This invention relates to a GaN-based Schottky diode with a vertical AlGaN / GaN heterojunction and its fabrication method, which can improve the current density per unit area and area utilization, and increase the forward current density of the diode.
[0038] The method for fabricating a GaN-based Schottky diode with a vertical AlGaN / GaN heterojunction according to the present invention includes the following steps:
[0039] I. For example Figure 1 As shown, an N is provided. + -GaN layer 1.
[0040] In this invention, the N + -GaN layer 1 serves as the substrate. Preferably, the N... + - The thickness of GaN layer 1 is 1~4μm.
[0041] II. Figure 2 As shown, in the N + - An N layer with a thickness of 3~9μm is grown on the front side of the GaN layer. - -GaN layer 2. The N - -GaN layer 2 is a drift layer.
[0042] Similar to existing technologies, in this invention, the N can be grown using an MOCVD (metal-organic chemical vapor deposition) process. --GaN layer 2.
[0043] III. Figure 3 As shown, in the N + -GaN layer 1 and N - -Etched groove a on GaN layer 2.
[0044] In this invention, the groove a can be etched using ICP (inductively coupled plasma) etching technology.
[0045] During etching, the width of the groove a is set to 3-5 μm. Furthermore, the depth of the groove a is set such that the N... + - The GaN layer 1 is etched away by 100~500 nm, that is, after etching away the N... - After GaN layer 2, a portion of the N layer thickness is then etched away. + -GaN layer 1, and make the N + The etching thickness of GaN layer 1 is 100-500 nm.
[0046] IV. Figure 4 As shown, an AlGaN layer with a thickness of 10~40nm is grown as a whole.
[0047] In this invention, the AlGaN layer 3 can also be grown using MOCVD (metal-organic chemical vapor deposition) technology. The AlGaN layer 3 must cover the N... - -GaN layer 2 and the bottom and sides of the groove a.
[0048] Preferably, during growth, the Al composition of the AlGaN layer is controlled to be 15% to 50%.
[0049] In this invention, an AlGaN / GaN heterojunction is formed by regrowing the AlGaN layer 3, and the AlGaN3 and the N - -GaN layer 2 forms 2DEG (two-dimensional electron gas) b in the vertical direction, but not in the horizontal direction. This reduces the N... - The equivalent resistance of the GaN layer 2 increases the forward current density of the diode. Simultaneously, the higher electron mobility of 2DEG results in better frequency characteristics for the diode.
[0050] V. For example Figure 5 As shown, in the N + A cathode 4 is fabricated on the bottom surface of GaN layer 1.
[0051] In this invention, preferably, the cathode 4 is composed of a Ti layer, an Al layer, a Ni layer and an Au layer stacked together, wherein the thickness of the Ti layer is 20 nm, the thickness of the Al layer is 160 nm, the thickness of the Ni layer is 55 nm and the thickness of the Au layer is 45 nm.
[0052] More preferably, after the cathode 4 is fabricated, a rapid metal annealing process is performed. This rapid metal annealing process involves rapid thermal annealing at 870°C in a N2 atmosphere for 30 seconds. Through this rapid metal annealing process, the ohmic contact metal used to fabricate the cathode 4 can be alloyed, facilitating the fabrication of the cathode 4.
[0053] VI. For example Figure 6 As shown, a dielectric layer 5 with a thickness of 0.1~1μm is deposited on the AlGaN layer 3.
[0054] In this invention, the dielectric layer 5 can be an Al2O3 layer, a SiN layer, or a SiO2 layer.
[0055] Furthermore, PECVD (plasma-enhanced chemical vapor deposition) process can be used when depositing the dielectric layer 5.
[0056] VII. For example Figure 7 As shown, etching away the N located at... - The portion above GaN layer 2, consisting of AlGaN layer 3 and dielectric layer 5, exposes the N-type GaN layer. - - Top surface of GaN layer 2.
[0057] In this invention, ICP (inductively coupled plasma) etching technology can also be used for etching.
[0058] 8. For example Figure 8 As shown, in the exposed N - - An anode groove c is etched on the top surface of GaN layer 2.
[0059] In this invention, the anode groove c can also be etched using ICP (inductively coupled plasma) etching technology.
[0060] Preferably, the depth of the anode groove c is 300-900 nm and the width is 3-6 μm.
[0061] IX. For example Figure 9 As shown, an anode 6 is fabricated within the anode groove c and on the remaining dielectric layer 5.
[0062] Preferably, the anode 6 is formed by stacking a Ni layer and an Au layer. The Ni layer has a thickness of 45 nm, and the Au layer has a thickness of 200 nm.
[0063] The present invention is described in more detail below with reference to several specific embodiments, so that those skilled in the art can implement the fabrication of the GaN-based Schottky diode having a vertical AlGaN / GaN heterojunction according to the description of the present invention.
[0064] The following embodiments have different anode groove etching depths, different AlGaN layer thicknesses, and different dielectric layers of different materials and thicknesses, but are otherwise identical.
[0065]
Example 1
[0066] In this embodiment, the etching depth of the anode groove c is 300 nm, the thickness of the AlGaN layer 3 is 20 nm and the Al composition is 25%, and the dielectric layer is a SiN dielectric layer with a thickness of 400 nm.
[0067] Therefore, the fabrication method of the GaN-based Schottky diode with a vertical AlGaN / GaN heterojunction in this embodiment includes the following steps:
[0068] Step 1. Epitaxial material growth.
[0069] In N with a thickness of 3μm + On GaN layer 1, an 8μm thick N-type N-type substrate was grown using MOCVD. - -GaN layer 2.
[0070] Step 2. Creation of regrowth grooves and regrowth.
[0071] 2.1) Fabrication of regrowth groove a
[0072] First, a spin coater is used to spin the photoresist at a speed of 3000 rpm. The photoresist used is AZ6130. Then, an NSR1755I7A lithography machine is used for exposure to form the area mask pattern of the groove a.
[0073] Then, the substrate with the mask prepared is etched using an ICP98c inductively coupled plasma etching machine in Cl2 plasma at an etching rate of 1 nm / s to etch the groove a to a depth of 8.4 μm.
[0074] 2.2) Regeneration of AlGaN layer 3
[0075] An AlGaN layer 3 with a thickness of 20 nm and an Al composition of 25% was deposited using an MOCVD deposition equipment.
[0076] Step 3. Electrode fabrication.
[0077] 3.1) Fabrication of cathode 4
[0078] First, the photoresist was spun at a speed of 5000 rpm using a spin coater to obtain a photoresist mask with a thickness of 0.8 μm.
[0079] Next, it was baked in a high-temperature oven at 80°C for 10 minutes, and then exposed using an NSR1755I7A lithography machine to form a cathode region mask pattern.
[0080] Then, the cathode was fabricated using an Ohmiker-50 electron beam evaporation stage at an evaporation rate of 0.1 nm / s. The ohmic metals were Ti / Al / Ni / Au in sequence, with Ti having a thickness of 20 nm, Al having a thickness of 160 nm, Ni having a thickness of 55 nm, and Au having a thickness of 45 nm. After the ohmic contact metal of the cathode was evaporated, the metal was stripped to obtain a complete cathode 4.
[0081] Finally, the ohmic contact metal is alloyed by rapidly annealing in an N2 atmosphere at 870°C for 30 seconds using an RTP500 rapid thermal annealing furnace, thus completing the fabrication of cathode 4.
[0082] 3.2) Growth of dielectric layer 5
[0083] A 400 nm thick SiN dielectric layer was deposited using a PECVD deposition equipment.
[0084] 3.3) Etching to remove N - -AlGaN layer 3 and dielectric layer 5 in the top part of GaN layer 2
[0085] First, a spin coater is used to spin the adhesive at a speed of 3500 rpm, and then an NSR1755I7A lithography machine is used for exposure to form N... - -Mask pattern of a portion of the top surface of GaN layer 2;
[0086] The masked substrate was then etched using an ICP98c inductively coupled plasma etching machine in Cl2 plasma at an etching rate of 1 nm / s, with an etching depth of 420 nm.
[0087] 3.4) Fabrication of the anode groove c
[0088] The photoresist was spun onto the surface of the epitaxial material at a speed of 5000 rpm to obtain a photoresist mask with a thickness of 0.8 μm. It was then baked in a high-temperature oven at 80℃ for 10 min. Finally, it was exposed using an NSR1755I7A lithography machine to obtain the photoresist mask of the anode groove c and the development was completed.
[0089] Next, an ICP98c inductively coupled plasma etching machine was used to etch and remove the 300 nm thick N-type ... --GaN layer 2, forming an anode groove c.
[0090] 3.5) Fabrication of Anode 6
[0091] First, a photoresist mask with a thickness of 0.8 μm was obtained by spinning the photoresist mask at a speed of 5000 rpm.
[0092] Next, it is baked in a high-temperature oven at 80°C for 10 minutes, and then exposed using an NSR1755I7A lithography machine to form a mask pattern for the anode region.
[0093] Finally, the anode metal was evaporated using an Ohmiker-50 electron beam evaporation stage at an evaporation rate of 0.1 nm / s. The anode metal was selected as Ni / Au, with a Ni thickness of 45 nm and an Au thickness of 200 nm. After evaporation, the metal was stripped to obtain a complete anode 6.
[0094]
Example 2
[0095] In this embodiment, the etching depth of the anode groove c is 600 nm, the thickness of the AlGaN layer 3 is 30 nm and the Al composition is 35%, and the dielectric layer 5 is a SiN dielectric layer with a thickness of 800 nm.
[0096] Therefore, the fabrication method of the GaN-based Schottky diode with a vertical AlGaN / GaN heterojunction in this embodiment includes the following steps:
[0097] Step 1. Epitaxial material growth.
[0098] In N with a thickness of 3μm + On GaN layer 1, an 8μm thick N-type ... - -GaN layer 2.
[0099] Step 2. Creation and regrowth of regrowth groove a.
[0100] 2.1) Fabrication of regeneration grooves
[0101] First, a spin coater is used to spin the photoresist at a speed of 3000 rpm. The photoresist used is AZ6130. Then, an NSR1755I7A lithography machine is used for exposure to form the mask pattern of the regrowth groove a region.
[0102] Then, the substrate with the mask prepared was etched using an ICP98c inductively coupled plasma etching machine in Cl2 plasma at an etching rate of 1 nm / s to etch the groove a to a depth of 8.4 μm.
[0103] 2.2) Regeneration of AlGaN layer 3
[0104] An AlGaN layer 3 with a thickness of 30 nm and an Al composition of 35% was deposited using an MOCVD deposition equipment.
[0105] Step 3. Electrode fabrication
[0106] 3.1) Fabrication of cathode 4
[0107] First, the photoresist was spun at a speed of 5000 rpm using a spin coater to obtain a photoresist mask with a thickness of 0.8 μm.
[0108] Next, it was baked in a high-temperature oven at 80°C for 10 minutes, and then exposed using an NSR1755I7A lithography machine to form the cathode 4 region mask pattern.
[0109] Then, the cathode was fabricated using an Ohmiker-50 electron beam evaporation stage at an evaporation rate of 0.1 nm / s. The ohmic metals were Ti / Al / Ni / Au in sequence, with Ti having a thickness of 20 nm, Al having a thickness of 160 nm, Ni having a thickness of 55 nm, and Au having a thickness of 45 nm. After the ohmic contact metal of the cathode was evaporated, the metal was stripped to obtain a complete cathode 4.
[0110] Finally, the ohmic contact metal is alloyed by rapidly annealing in an N2 atmosphere at 870°C for 30 seconds using an RTP500 rapid thermal annealing furnace, thus completing the fabrication of cathode 4.
[0111] 3.2) Growth of dielectric layer 5
[0112] A SiN dielectric layer with a thickness of 800 nm was deposited using a PECVD deposition equipment.
[0113] 3.3) Etching to remove N — AlGaN layer 3 and dielectric layer 5 in a partial area on the top surface of GaN layer 2
[0114] First, a spin coater is used to spin the adhesive at a speed of 3500 rpm, and then an NSR1755I7A lithography machine is used for exposure to form N... - - Mask pattern of a portion of the top surface of GaN layer 2;
[0115] The masked substrate was then etched using an ICP98c inductively coupled plasma etching machine in Cl2 plasma at an etching rate of 1 nm / s, with an etching depth of 830 nm.
[0116] 3.4) Fabrication of the anode groove c
[0117] The photoresist mask was spun onto the surface of the epitaxial material at a speed of 5000 rpm to obtain a thickness of 0.8 μm. It was then baked in a high-temperature oven at 80℃ for 10 min. Finally, it was exposed using an NSR1755I7A lithography machine to obtain the anode groove c photoresist mask and complete the development.
[0118] Next, an ICP98c inductively coupled plasma etching machine was used to etch and remove the 600 nm thick N-type ... - -GaN layer, forming anode groove c.
[0119] 3.5) Fabrication of Anode 6
[0120] First, a photoresist mask with a thickness of 0.8 μm was obtained by spinning the photoresist mask at a speed of 5000 rpm.
[0121] Next, it is baked in a high-temperature oven at 80°C for 10 minutes, and then exposed using an NSR1755I7A lithography machine to form a mask pattern for the anode region.
[0122] Finally, the anode metal was evaporated using an Ohmiker-50 electron beam evaporation stage at an evaporation rate of 0.1 nm / s. The anode metal was selected as Ni / Au, with a Ni thickness of 45 nm and an Au thickness of 200 nm. After evaporation, the metal was stripped to obtain a complete anode 6.
[0123]
Example 3
[0124] In this embodiment, the etching depth of the anode groove c is 900 nm, the thickness of the AlGaN layer 3 is 40 nm and the Al composition is 45%, and the dielectric layer 5 is a SiO2 dielectric layer with a thickness of 600 nm.
[0125] Therefore, the fabrication method of the GaN-based Schottky diode with a vertical AlGaN / GaN heterojunction in this embodiment includes the following steps:
[0126] Step 1. Epitaxial material growth.
[0127] In N with a thickness of 3μm + On GaN layer 1, an 8μm thick N-type N-type substrate was grown using MOCVD. - -GaN layer 2.
[0128] Step 2. Creation of regrowth grooves and regrowth.
[0129] 2.1) Fabrication of regrowth groove a
[0130] First, a spin coater is used to spin the photoresist at a speed of 3000 rpm. The photoresist used is AZ6130. Then, an NSR1755I7A lithography machine is used for exposure to form the mask pattern of the regrowth groove a region.
[0131] Then, the substrate with the mask prepared was etched using an ICP98c inductively coupled plasma etching machine in Cl2 plasma at an etching rate of 1 nm / s to etch the groove a to a depth of 8.4 μm.
[0132] 2.2) Regeneration of AlGaN layer 3
[0133] An AlGaN layer 3 with a thickness of 40 nm and an Al composition of 45% was deposited using an MOCVD deposition equipment.
[0134] Step 3. Electrode fabrication.
[0135] 3.1) Fabrication of cathode 4
[0136] First, the photoresist was spun at a speed of 5000 rpm using a spin coater to obtain a photoresist mask with a thickness of 0.8 μm.
[0137] Next, it was baked in a high-temperature oven at 80°C for 10 minutes, and then exposed using an NSR1755I7A lithography machine to form a cathode region mask pattern.
[0138] Then, the cathode was fabricated using an Ohmiker-50 electron beam evaporation stage at an evaporation rate of 0.1 nm / s. The ohmic metals were Ti / Al / Ni / Au in sequence, with Ti having a thickness of 20 nm, Al having a thickness of 160 nm, Ni having a thickness of 55 nm, and Au having a thickness of 45 nm. After the ohmic contact metal of the cathode was evaporated, the metal was stripped to obtain a complete cathode 4.
[0139] Finally, the ohmic contact metal is alloyed by rapidly annealing in an N2 atmosphere at 870°C for 30 seconds using an RTP500 rapid thermal annealing furnace, thus completing the fabrication of cathode 4.
[0140] 3.2) Growth of dielectric layer 5
[0141] A SiO2 dielectric layer with a thickness of 600 nm was deposited using a PECVD deposition equipment.
[0142] 3.3) Etching to remove N - - Partial area of AlGaN layer 3 and dielectric layer 5 on the top surface of GaN layer 2
[0143] First, a spin coater is used to spin the adhesive at a speed of 3500 rpm, and then an NSR1755I7A lithography machine is used for exposure to form N... -- Partial mask pattern on the top surface of GaN layer 2;
[0144] The masked substrate was then etched using an ICP98c inductively coupled plasma etching machine in Cl2 plasma at an etching rate of 1 nm / s, with an etching depth of 640 nm.
[0145] 3.4) Fabrication of the anode groove c
[0146] The photoresist mask was spun onto the surface of the epitaxial material at a speed of 5000 rpm to obtain a thickness of 0.8 μm. It was then baked in a high-temperature oven at 80℃ for 10 min. Finally, it was exposed using an NSR1755I7A lithography machine to obtain the anode groove c photoresist mask and complete the development.
[0147] Next, an ICP98c inductively coupled plasma etching machine was used to etch and remove the 900 nm thick N-type ... - -GaN layer 2, forming an anode groove c.
[0148] 3.5) Fabrication of Anode 6
[0149] First, a photoresist mask with a thickness of 0.8 μm was obtained by spinning the photoresist mask at a speed of 5000 rpm.
[0150] Next, it is baked in a high-temperature oven at 80°C for 10 minutes, and then exposed using an NSR1755I7A lithography machine to form a mask pattern for the anode region.
[0151] Finally, the anode metal was evaporated using an Ohmiker-50 electron beam evaporation stage at an evaporation rate of 0.1 nm / s. The anode metal was selected as Ni / Au, with a Ni thickness of 45 nm and an Au thickness of 200 nm. After evaporation, the metal was stripped to obtain a complete anode 6.
[0152] Compared to traditional GaN-based vertical diodes, this invention utilizes a regrown AlGaN layer to form a 2DEG (two-dimensional electron gas) in the vertical direction, reducing N0. - The equivalent resistance of the GaN layer increases the forward current density of the diode; simultaneously, the higher electron mobility of the 2DEG channel results in better frequency characteristics. Furthermore, compared to the horizontal conductivity of traditional AlGaN / GaN diodes, this invention employs a vertical 2DEG channel, increasing the current density per unit area and thus improving the diode's area utilization.
[0153] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention. Those skilled in the art can modify or make equivalent substitutions to the technical solutions of the present invention based on the concept of the present invention, without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A method for fabricating a GaN-based Schottky diode with a vertical AlGaN / GaN heterojunction, characterized in that, Includes the following steps: 1) In N with a thickness of 1~4μm + - A layer of N with a thickness of 3~9μm is grown on the front side of the GaN layer (1). - -GaN layer (2); 2) In the N + -GaN layer (1) and N - - A groove (a) is etched on the GaN layer (2), the width of the groove (a) being 3~5μm and the depth being such that the N... + - The GaN layer (1) is etched away by 100~500 nm; 3) Grow an AlGaN layer with a thickness of 10~40nm as a whole (3); 4) In the N + - A cathode (4) is fabricated on the bottom surface of the GaN layer (1). 5) Deposit a dielectric layer (5) with a thickness of 0.1~1μm on the AlGaN layer (3); 6) Etch away the N located in the N - -The portion above the GaN layer (2) consists of the AlGaN layer (3) and the dielectric layer (5), exposing the N-type GaN layer. - - Top surface of GaN layer (2); 7) In the exposed N - - An anode groove (c) is etched on the top surface of the GaN layer (2), and the depth of the anode groove (c) is 300-900nm; 8) Fabricate an anode (6) in the anode groove (c) and on the remaining dielectric layer (5); Wherein, the AlGaN layer (3) and the N - - A two-dimensional electron gas (b) is formed between the GaN layers (2) in the vertical direction and no two-dimensional electron gas is formed in the horizontal direction. After step 4), a rapid metal annealing process is performed first, and then step 5) is performed. The rapid metal annealing process is a rapid thermal annealing at a temperature of 870°C in a N2 atmosphere for 30 seconds.
2. The method for fabricating a GaN-based Schottky diode with a vertical AlGaN / GaN heterojunction according to claim 1, characterized in that, The Al composition of the AlGaN layer (3) is 15%~50%.
3. The method for fabricating a GaN-based Schottky diode with a vertical AlGaN / GaN heterojunction according to claim 2, characterized in that, The dielectric layer (5) is an Al2O3 layer, a SiN layer, or a SiO2 layer.
4. The method for fabricating a GaN-based Schottky diode with a vertical AlGaN / GaN heterojunction according to claim 3, characterized in that, The cathode (4) is composed of a Ti layer, an Al layer, a Ni layer and an Au layer stacked together, wherein the thickness of the Ti layer is 20 nm, the thickness of the Al layer is 160 nm, the thickness of the Ni layer is 55 nm and the thickness of the Au layer is 45 nm.
5. The method for fabricating a GaN-based Schottky diode with a vertical AlGaN / GaN heterojunction according to claim 4, characterized in that, The anode (6) is composed of a Ni layer and an Au layer stacked together, wherein the thickness of the Ni layer is 45 nm and the thickness of the Au layer is 200 nm.
6. A GaN-based Schottky diode with a vertical AlGaN / GaN heterojunction, characterized in that, It is prepared using the preparation method described in any one of claims 1-5.
Citation Information
Patent Citations
Longitudinal conduction-type GaN-based groove junction barrier Schottky diode and manufacturing method thereof
CN105405897A
